Perceptions of hotel workers affected by the pandemic on stocks - Parwati, Komang Shanty Muni; Kuntariati, Utik; Amir, Firlie Lanovia (Journal of Business on Hospitality and Tourism, 2021)
The Covid-19 pandemic has become a momentum for major changes for tourism workers, who have largely lost their livelihoods and are experiencing economic hardship. The corona virus outbreak has led to massive job losses and reductions in income across Bali. Covid-19 restrictions are ravaging the tourism sector which is the main source of economy for Balinese and its surrounding island. Many have returned to their hometowns. And not being able to pay for the necessities of life, such as boarding house, electricity, food, and the difficulty of paying the existing instalments. The purpose of this study is to examine how the views and enthusiasm of hotel workers at the operational level towards stock investment. This quantitative descriptive research used mix methods from 89 respondents aged 20-50 years, both from the back office and front office staff. The result of this research is that stocks become an acceptable instrument for workers aged 20-30. Stock literacy only works for millennial generation operational workers and back-office workers. Stock literacy is given with more frequency by creating WhatsApp group discussion. So that the understanding of stocks will improve.